2002
DOI: 10.1111/j.1752-1688.2002.tb00995.x
|View full text |Cite
|
Sign up to set email alerts
|

POTENTIAL IMPACT OF EARTHEN WASTE STORAGE STRUCTURES ON WATER RESOURCES IN IOWA1

Abstract: Earthen waste storage structures (EWSS) associated with large confined (concentrated) animal feeding operations (CAFOs) were evaluated for their potential to impact water resources in Iowa. A representative sample of 34 EWSS from a digital database of 439 lagoons and basins permitted between 1987 and 1994 was analyzed. Eighteen percent (6 of 34) directly overlie alluvial aquifers that are used widely for potable water supply. Ninety‐four percent (29 of 31) were constructed below the water table based on EWSS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…T ill units of Pre‐Illinoian to late Wisconsinan age have generally been viewed as impermeable materials that preclude vertical and horizontal transport of surficial contaminants to aquifers and surface waters in Iowa. This idea has been extended to point sources such as landfills and hazardous waste sites and nonpoint sources including surface‐applied nutrients and herbicides, and seepage of effluent from sewage and swine manure lagoons (Simpkins et al, 2002). Studies have suggested, however, that significant nitrate and herbicide contamination of the underlying aquifers has occurred in many areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T ill units of Pre‐Illinoian to late Wisconsinan age have generally been viewed as impermeable materials that preclude vertical and horizontal transport of surficial contaminants to aquifers and surface waters in Iowa. This idea has been extended to point sources such as landfills and hazardous waste sites and nonpoint sources including surface‐applied nutrients and herbicides, and seepage of effluent from sewage and swine manure lagoons (Simpkins et al, 2002). Studies have suggested, however, that significant nitrate and herbicide contamination of the underlying aquifers has occurred in many areas.…”
mentioning
confidence: 99%
“…This idea has been extended to point sources less than the total porosity ( T ) of till (McKay et al, such as landfills and hazardous waste sites and nonpoint 1993a; Jørgensen et al, 1998). Advective velocity of sources including surface-applied nutrients and herbisolutes in fractured systems may be estimated by the cides, and seepage of effluent from sewage and swine average linear velocity equation: manure lagoons (Simpkins et al, 2002). Studies have…”
mentioning
confidence: 99%
“…Moreover, one Iowa study found that more than half of the manure storage structures tested leaked at rates above the legal limit. 12 There are approximately 5600 such structures in the state. The Environmental Integrity Project report documented 329 manure spills in Iowa between 1992 and 2002.…”
Section: 10mentioning
confidence: 99%
“…Animal waste management is an important component of controlling nonpoint source pollution. Simpkins et al (2002b) looked at the potential impact of earthen waste storage structure (EWSS) on water resources in Iowa. They found that a large number of EWSS associated with large confined (concentrated) animal feeding operations (CAFOs) have a greater potential to impact water resources.…”
Section: Dukes Et Al (2002) Evaluated the Effect Of Riparian Buffer mentioning
confidence: 99%